BS37 Understanding the germinal centre B cell response to atherosclerosis in mice using lineage tracing. (May 2019) - Francis, Anne; Sage, Andrew
Abstract : Introduction: Elevated plasma low density lipoprotein (LDL) is a major risk factor for atherosclerosis and its immunogenic oxidation triggers an inflammatory response. The importance of B cells within cardiovascular disease is demonstrated by genome-wide association studies and transcriptomic studies that have identified genes involved in proliferation and activation of B cells. It has been shown that the germinal centre (GC) response, the process by which plasma and memory B cells are formed, is pathogenically dysregulated in atherosclerosis, and that class-switched plasma cells infiltrate into human diseased vascular tissue. We therefore sought to further characterise and understand the causes for this pathogenic response by using a lineage tracing mouse model. Methods: Use of the tamoxifen-inducible AID-CreERT2-Rosa-EYFP-Ldlr-/- lineage tracing mouse model enables the tracking of atherosclerosis-specific B cell clones comprising GC, memory and plasma B cells. Ldlr-/- and Ldlr± ('WT') mice were fed chow or western diet (WD) for up to 8 weeks and upon tamoxifen dosing via intra-peritoneal injection, AID-expressing cells (GC B cells) are fluorescently labelled with EYFP. The timing of tamoxifen dosing was varied throughout the studies. Results: Ldlr-/- mice develop an enlarged GC response within the spleen and lymph nodes, although not in gut-associated Peyer's patches. Around 50% of Ldlr-/- mice on chow diet develop this response whereas >80% of WD-fed mice have an enhanced response. WT mice do not develop this response. The GC response consists of more class-switched (IgM-) GC B cells in Ldlr-/- mice compared to WT mice. This results in increased serum levels of the Th1-driven IgG isotype IgG2c, but no increase in Th2-driven IgG1 after 8 weeks western diet. Labelling GC cells during western diet (but not before) demonstrates that GC clones persist longer after western diet feeding than in chow-fed mice. Conclusion: Atherosclerotic conditions increase not only numbers of GC B cells, but also change the type of response that occurs, providing an opportunity to target the atherosclerosis-specific responses therapeutically. Conflict of interest: None